Development of Data Acquisition and Measurement Software for Neutron Triple Axis Spectrometer at BATAN-Serpong, Indonesia - B Bharoto; S Sairun; A. Ramadhani; I. Sumirat (Atom Indonesia, 2017)
The Neutron Scattering Laboratory at the National Nuclear Energy Agency of Indonesia (BATAN) possesses several neutron beam instruments for materials science research. One of the instruments is a neutron triple-axis spectrometer (TAS). Due to the malfunction of the main computer, the original main control system had to be replaced with a new one. For this reason, a new data acquisition and measurement software program based on GNU C++ programming language was developed for restoring the spectrometer's functionality. However, using the resulting control system, triple-axis mode experiments were very difficult to perform and their types that can be performed were limited. In order to conduct the experiments more effectively and efficiently, several improvements in both hardware and software have been developed. The Visual Basic programming language was used in developing the data acquisition and measurement software that makes it possible for all motors to move simultaneously, so that the time spent for the experiments is reduced significantly. Also, programmable motor controller cards were used for driving all the 23 motors of the instrument. All the 23 axes can be controlled by clicking the appropriate buttons or inputting text command in the main window of the software's user interface. The software has also been used to perform an elastic experiment, as well as an inelastic experiment for investigating the phenomenon of phonon. The software developed is more user friendly than the older ones, since the spectrometer status and the experiment results can be displayed in real time at the windows, and it also makes experiments more effective and efficient since the experiments can be automated and run without any user intervention until the experiments finish.